2014
DOI: 10.1259/bjr.20140398
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic radiotherapy against heterotopic ossification following internal fixation of acetabular fractures: a comparative estimate of risk

Abstract: The risk from RT prophylaxis is small, it is safer than indometacin and substantially overlaps with the range for no prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
(106 reference statements)
0
14
0
2
Order By: Relevance
“…However, recent studies have shown the efficacy of a single dose of 6–8 Gy, administered at energies between 6 and 15 MV. 133,134 Prophylactic radiation also reduces the recurrence of HO after resection of heterotopic bone, as has been extensively demonstrated in case of knee replacement surgeries. 135 Despite the predominance of RT use toward HO prophylaxis, there are side-effects associated with its use, such as, increase in bony nonunions, and radiation-induced sarcoma.…”
Section: Treatment and Prophylaxismentioning
confidence: 91%
“…However, recent studies have shown the efficacy of a single dose of 6–8 Gy, administered at energies between 6 and 15 MV. 133,134 Prophylactic radiation also reduces the recurrence of HO after resection of heterotopic bone, as has been extensively demonstrated in case of knee replacement surgeries. 135 Despite the predominance of RT use toward HO prophylaxis, there are side-effects associated with its use, such as, increase in bony nonunions, and radiation-induced sarcoma.…”
Section: Treatment and Prophylaxismentioning
confidence: 91%
“…The number of studies looking at this modern regimen are very limited and thus our literature review only yielded only a few relevant studies. Burnet et al in 2014 reported on a cohort of 34 patients who underwent RT in a single fraction of 8 Gy for the prevention of HO after traumatic acetabular fracture; 28 (82%) developed no HO, 6 (17.6%) developed clinically Brooker grade I HO, and none developedBrooker grade II-IV HO 21.…”
mentioning
confidence: 99%
“…This study showed that the risks from RT prophylaxis were small and that RT was safer than indometacin and substantially overlapped with the range for no prophylaxis. 107 Clearly RT offers a good control, although the risk of a RIC will be unknown for many years; in these older patients, it is likely to be very small.…”
mentioning
confidence: 99%